QIU, Z.J., WANG, X.L., LIU, Z.Y., YANG, J.F. & ZHANG, S.Z. (2012) Cytological and phylogenetic study of Petrocosmea hexiensis (Gesneriaceae), a new species from Chongqing, China. Phytotaxa, 74, 30–38. - Qiu, Z.j.; Wang, X.l.; Liu, Z.y.; Yang, J.f.; Zhang, S.z. (Phytotaxa, 2013)
Please note the following information should be added to the author:XIAO-LING WANG1,3,††Equal contributor